The Comparison of Personality characteristics and Clinical syndrome owners Pets keeper and People without Pets - ezzatinia, mohammad javad; esmaeeli, sona (Iranian Journal of Educational Sociology, 2022)
AbstractIntroduction: The aim of this study was to evaluate the Comparison of Personality characteristics and Clinical syndrome owners Pets keeper and People without Pets.Methodology: The research method was causal-comparative. The statistical population included all pets and non-domestic animals resident in the 20th district of Tehran in 2018. The sample consisted of 160 individuals with pets (80) and non-pets (80) who were selected based on available sampling. Measurement tool was McCrae and Costa's Personality characteristics questionnaire (1992) and clinical checklist Drogates and colleagues (1973). Data analysis was carried out through questionnaire implementation through spss22 software in two descriptive and inferential sections (Multivariable Analyze of Variance).Findings: The results showed that the difference between the two groups was significant in all personality traits, except for neuroticism. According to the comparison of the averages, it is evident that pet owners and owners have extraversion, less openness to experience, duty, and acceptability than non-pet animals. Also, the results of multivariate analysis of clinical syndrome showed that the difference between the two groups in all clinical syndromes was significant except for obsessive-compulsive disorder.Conclusion:  Regarding the comparison of the averages, it was found that pets owning and having pets have higher levels of physical complaints, interpersonal sensitivity, depression, anxiety, aggression, paranoid thoughts, and psychosis.